VALORAÇÃO ECONÔMICA DE SERVIÇOS AMBIENTAIS NOS SISTEMAS AGROFLORESTAIS - SAFS DO MUNICÍPIO DE DOURADOS, MS. - Andrade, Gabriela; Ferreira, Luciana; padovan, Milton; Silva, Jaqueline (ANAIS DO ENIC, 2018)
-